The JAK2V617F mutation and the role of therapeutic agents in alleviating myeloproliferative neoplasm symptom burden - Lai Yee Orbell; Nouf Abutheraa; Andrew S Duncombe; Mary Frances McMullin; Ruben Mesa; Charlene M McShane; Glen James; Lesley A Anderson (eJHaem, 2023)
Abstract Alleviating symptom burden in patients with myeloproliferative neoplasms (MPNs) is imperative to achieving optimal management. Research remains to elucidate the relationship between the JAK2V617F (Janus kinase 2) mutation present in many MPN patients, and the symptomatology they experience. This retrospective study analysed data collected from MPN patients included in the Myeloproliferative Neoplasms: An In‐depth Case–Control (MOSAICC) pilot study. The MPN Symptom Assessment Form was administered, and median symptom scores were compared between JAK2V617F‐positive and JAK2V617F‐negative groups. Multivariate logistic regression analysis adjusted for confounding variables. Overall, 106 MPN patients participated: 65.1% were JAK2V617F positive, 30.2% were JAK2V617F negative and 4.7% had an unknown status. Multivariate analysis revealed a low symptom burden for early satiety (p < 0.01), dizziness (p < 0.05), cough (p < 0.05) and bone pain (p < 0.01) in those receiving venesection alone. Interferon alpha was significantly associated (p < 0.05) with severe burden for 16 of the 27 symptoms. JAK2V617F‐positive females experienced a greater symptom burden than JAK2V617F‐positive males. There was no discernible relationship between the JAK2V617F mutation and symptom burden in MPN patients, unlike the therapeutic agents investigated. Larger studies are required to validate these results and identify mechanisms of symptom development and control in MPN patients.